HUBUNGAN SEGITIGA ANTARA BIROKRAT PENGUSAHA DAN POLITIKUS PARTAI DEMOKRASI LIBRAL (JIMINTOO) DALAM PEMILIHAN UMUM DI JEPANG - Sendra, I Made (E-Jurnal Kajian Budaya (Online Journal of Cultural Studies), 2014)
In Japan, after The Second World War, the pressure groupscame from big companies, which had important role toredevelop Japanese industries. Due to the fact that theywere involved in establishing the economic policiessince 1950, the political life style was expressed asthough the domination of triangle’s strength, such as; theLiberal Democracy Party (LDP) politician, bureaucrat,and businessman. Businessman (industrialist) as oneof pressure groups wanted to control the government ofruling party to give political finance.The pressure group, such as, Zaikei (the groupof big companies), they got unilateral eases in terms ofregulation, clearance and act. Nevertheless, the trianglerelation was not permanent because the economic growthhad made pollution and urbanization. It made contradictionto the politician’s interest. The Japanese people prosecutedthe LDP politician and bureaucrat to restrain the pollutionand increase the social welfare and the life quality. Thepressure group used many ways to influence and to controlthe government’s policies by making Advisory Board(Shingikai) which was consisted of professional andcommon people.The collusion, corruption and bribe scandal cameinto the fore involving the former Japanese prime ministerswho were from the LDP politicians. They were causedby some factors such as: (a) the Japanese culture and thepolitician morality; (b) the election system of the House of Representatives members; (c) the competition amongthe faction of LDP to become the president of LDP, whichhave a chance to be the Japanese prime minister.